Teacher Development to Augment Pedagogical Competence in Society 5.0 - Sabariah, Sabariah; Hakim, Luqmanul; Kadori, Kadori; Zahra, Annisa; Muin, Abdul (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This research aims to analyze and describe the process of enhancing teachers' pedagogical competence in Society 5.0. A qualitative research methodology was employed, utilizing a case study approach. Data were collected through interviews with one principal, one vice principal, six teachers, and one administrative staff member. Data processing techniques included reduction, data presentation, and conclusion drawing. The validity of the data was ensured through credibility and confirmability. The findings indicate three stages of teacher development: (a) Awareness and behavior formation stage, which involves training needs analysis, learning design, access to self-contained material centers, teacher motivation, moral and material support, performance assessment, Yaumiyah, Tastqif, and Tahfidzul Qur'an programs. (b) The ability transformation stage focused on education quality, the application of independent learning, and learning design. (c) The ability enhancement stage involved IT-based learning and teacher collaboration. The outcomes of teacher development encompassed competence mapping, student mentoring, identification of developmental needs, fostering Islamic personality, nurturing character-driven teachers, employing Student-Centered and Project Learning models, and an increase in teachers' knowledge.